Separation of rotamers of 5-nitrosopyrimidines and estimation of binding constants of their complexes with β-cyclodextrin by capillary electrophoresis - Štěpánová, Sille; Procházková, Eliška; Čechová, Lucie; Žurek, Jiří; Janeba, Zlatko; Dračínský, Martin; Kašička, Václav (Journal of chromatography. A, 2018)
For the first time, capillary electrophoresis has been successfully employed for the fast and highly efficient separations of a novel type of stereoisomers - planar rotamers (planamers) of four newly synthesized 5-nitrosopyrimidine derivatives. These derivatives can form two rotamers differing in the orientation of nitroso group due to strong intramolecular hydrogen bonds. Partial separation of rotamers of two 5-nitrosopyrimidines was achieved in alkaline 50 mM sodium tetraborate, pH 9.3, and in acidic 18.5/42 mM Tris/phosphate, pH 2.3, background electrolytes (BGEs) free of stereoselectors. To improve the separation of these rotamers and to attain the baseline or better separation of rotamers of other two 5-nitrosopyrimidines, various BGEs and different cyclodextrins-based stereoselectors were tested. The most effective, i.e. the fastest and baseline or better separations of rotamers of all analyzed 5-nitrosopyrimidines were achieved within a short time, 3.7-9.3 min, in the above alkaline or acidic BGEs using β-cyclodextrin (β-CD) or carboxymethyl-β-CD as stereoselectors. Moreover, since the experiments with β-CD resulted in good separations of rotamers of all the investigated 5-nitrosopyrimidines, the apparent binding constants of their complexes with this selector were determined from the dependence of their effective mobilities on the β-CD concentration in the BGEs. The examined complexes were found to be relatively weak, with the apparent binding constants in the range 11.3-153.0 L/mol.
Keywords: Capillary electrophoresis; vodíková vazba; pyrimidiny; Electrophoresis, Capillary; Hydrogen-Ion Concentration; elektroforéza kapilární; elektrolyty; Planar rotamers; nitrososloučeniny; Stereoisomerism; stereoizomerie; Electrolytes; 5-Nitrosopyrimidines; Binding constant; Hydrogen Bonding; beta-cyklodextriny; Nitroso Compounds; beta-Cyclodextrins; Affinity capillary electrophoresis; koncentrace vodíkových iontů; Pyrimidines; Cyclodextrins